(3CUhd JQcjH GdCOhjIs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s ((3eMeO Hf YHO Gddg GdTeS GdJSJQi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd GdTjN Ef GdhGLH Ydi cd Pi dH Cf jJbQH Edi Gddg JYGdi hjJhSd Edjg , Hcd eG jJjSQ dg ef GdbQHGJ , hCMSf GdhSGFd eGjYhO Ydi faY GdeSdejf YGeI , hjQLY Edi OaY GdCPi Yfge s
(3BNQgG (B:s
(3hbO jLYd HOd GdYaU EPG de jQO Hg TOI GdShGO s
(3Vef eLehY , JQJjHgG (B: (3ef U (B221 - (3U(B255s
(3GdbSe GdKGdK ef GdfLjHjGJs
(3hGfXQ agQS GdWH HQbe (B13 " (3CUhd JQcjH GdCOhjI (B"s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
Keywords: (3GdWHs